Schindler/Moscheles Lock of Beethoven's Hair and related materials in mat (2023)
Framed object containing a lock of hair attributed to Beethoven, cut from Beethoven's head by Anton Felix Schindler on March 24, 1827 and given to Ignaz Moscheles after Beethoven's death; later matted and framed with a portrait sketch of Beethoven by Felix Moscheles and leaves from Beethoven's grave collected by George Doane, intended as a gift for Robert Schumann. With portrait sketch of an unidentified girl on verso of Beethoven portrait.